Qualitative Study and Antioxidant Activity Herbal Tea Bag of Moringa Leaves (Moringa oleifera Lam.) and Red Ginger (Zingiber officinale var. Rubrum) - Tenda, Priska Ernestina; Hilaria, Maria; Soeharto, Faizal R.; Najib, Mohd Nadzri Bin Mohd (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Moringa (MO) leaves contain several chemical substances of high value, including vitamin C, flavonoids, phenolic compounds, carotenoids, tannins, and triterpenoids, among which one functions as an antioxidant. Previous research observed that MO leaves have already been developed into various formulations; unfortunately, these formulas could not completely obscure the aroma and taste problems that rendered MO leaves less acceptable to consumers. In this research, Moringa leaf powder (MLP) and red ginger (RG) are combined to cover the unpleasant taste and aroma of MO leaves. The purpose of this study assess the quality of three tea bag formulations, including their water content, ash content, hedonic and antioxidant activities, by quantitative tests; F0 (3 Gr of MLP), F1 (2.25 Gr of MLP, and 0.75 Gr of RG), and F2 (the amount of MLP and RG is equal to 1.5 Gr). This experimental study employs a completely randomized design, three special treatments, and three repetitions. Statistical analysis of quality test results and antioxidant activity uses One-Way ANOVA followed by a post hoc test utilizing the Least Significant Difference (LSD). The water content tests revealed that all three formulations qualified the Indonesian National Standard (SNI), ranging from 3.86% to 4.29%. Adding ginger did not influence the water content (p > 0.05). Otherwise, it increases the ash level from 8.65% to 9.98%. Based on the results of the hedonic test, the panelists preferred F0 over F1 and F2 concerning color by a score of 86%. In contrast, they preferred F2 regarding aroma and taste by a score of 82%. The addition of RG in F1 and F2 was significant to the preference level of panelists ('p <0.05). The IC50 value for the antioxidant activity test was highest for F2 at 59.31 ± 0.13 ppm. The addition of RG boosted the antioxidant activity of MO tea products considerably (sig <0.05). Consequently, developing MO tea products containing RG in F2 could be potentially produced as herbal tea beverages with antioxidant properties.